Network Pharmacologic Analysis of Dendrobium officinale Extract Inhibiting the Proliferation of Gastric Cancer Cells - Lianping Wei; Wenhao Dong; Zhen Han; Chen Chen; Qing Jin; Jinling He; Yongping Cai (Frontiers Media S.A., 2022)
Globally, gastric cancer (GC) is one of the three most deadly cancers. Dendrobium officinale (D. officinale) is a traditional Chinese medicine (TCM), and its extract can significantly inhibit the proliferation of gastric cancer cells. However, there are no unified conclusions on its potential active components and possible mechanisms of action. This paper aims at exploring the potential active components, targets, and cell pathways of D. officinale extract in inhibiting the proliferation of gastric cancer cells by using network pharmacology and cytology experiments. In this paper, UPLC-MS/MS was used to identify the main chemical components in the extracts of D. officinale, and the an ADME model was used to screen the potential active components. Network pharmacology methods such as target prediction, pathway identification, and network construction were used to determine the mechanism through which the D. officinale extract inhibited gastric cancer cell proliferation. MTT assays, fluorescence confocal microscopy, clone formation, and flow cytometry were used to verify the inhibitory activity of the D. officinale extract on gastric cancer cell proliferation in vitro. The UPLC-MS/MS analysis identified 178 chemical components from the D. officinale extract. Network pharmacology analysis showed that 13 chemical components had the potential to inhibit the proliferation of gastric cancer cells, with the possible involvement of 119 targets and 20 potential signaling pathways. In vitro experiments confirmed that the D. officinale extract could significantly inhibit the proliferation of gastric cancer cells. Therefore, we believe that the D. officinale extract can inhibit the proliferation of gastric cancer cells through effects on multiple components, multiple targets, and multiple pathways.